(untitled) (Research, Society and Development, 2023)
Introduction: parotid gland neoplasms correspond to most neoplasms that affect the salivary glands, having different histological types. Among them, the most common are Warthin’s tumor and pleomorphic adenoma. Each histological type has different risk factors and predominance in different genders. Objective: this study aims to retrospectively analyze patients diagnosed with parotid neoplasms, seeking to identify anatomopathological characteristics, incidence in relation to age group and sex, possible risk factors, treatments performed and postoperative complications in the period from 2014 to 2020. at the Cascavel Cancer Hospital - União Oeste Paranaense de Combate ao Câncer - Uopeccan. Methods: 195 medical records were analyzed, all from 2014 to 2020, from these records the necessary data for this study were taken and tabulated, with the objective of defining the profile of the patients studied. Results: The most frequent malignant neoplasm was SCC- (metastatic squamous cell carcinoma). Warthin’s Tumor has also been shown to be strongly associated with smoking. Conclusion: the profile of the patients at Hospital Uopeccan correspond to the profile of the world literature, however there was a higher incidence of metastatic SCC in relation to mucoepidermoid carcinoma. A possible risk factor for Warthin’s Tumor would be smoking. The most commonly presented primary malignant neoplasm was carcinoma ex pleomorphic adenoma.